Danian cold‐water corals from the Baunekule facies, Faxe Formation, Denmark: a rare taphonomic window of a coral mound flank habitat. (4th January 2014) - Lauridsen, Bodil W.; Bjerager, Morten
<x xml:space="preserve">Abstract</x> Well‐preserved cold‐water corals are comparatively rare in the fossil record. This is partly due to the very low fossilization potential of the predominantly aragonitic corals but also due to the fact that coral ecosystems of deep water are a geologically young development. A Middle Danian cold‐water coral mound complex is well exposed in Faxe Quarry, Denmark. The coral mounds are intercalated with bryozoan mounds of various sizes and form the Faxe Formation. The coral limestone displays large variations in diagenesis, and this complicates the palaeoecological reconstructions. However, the Baunekule facies from the Faxe Formation contain a well‐preserved originally aragonitic and calcitic fauna. The aragonitic skeletons have been recrystallized to calcite during early diagenesis and the excellent preservation makes taxonomic identifications straightforward. A diverse fauna of ten scleractinian coral species, nine stylasterine coral species and seven octocoral species has been described from the Baunekule facies. The fossil fauna represents an ecological niche between the dead coral framework and coral rubble on a flank of a growing Dendrophyllia coral mound with multiple colonization events. The diversity and relative abundance of the fossil scleractinian corals are comparable to the modern settings in the NE Atlantic and Mediterranean. The distribution and diversity of the octocorals and the stylasterine corals are suggested to represent coral gardens as described from modern setting in the NE Pacific. The presence of a diverse and abundant stylasterine fauna suggests a stable palaeoenvironment, probably in a bathymetric depth range of 200–400 metre.